ECONOMETRIC MODEL OF FIRM’S VALUE IN LIQUID MARKET: CASE OF INDONESIA - Putu Agus Ardiana (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2012)
The research aims to investigate variables affecting Tobin’s Q which represents the value of public  companies listed on LQ45 Index on the Indonesia Stock Exchange by developing a  BLUE(Best Linear UnbiasedEstimators) econometric model for cross-sectional data of 2007, 2008, and 2009 as well as panel data. The models vary across different data but there are important findings to note. Public companies listed  on LQ45 Index have experienced overliquidity problem during the period of observation leading to a decline in firm’s value. In addition, those public companies have low financial risk so they have chance to  increase their debts especially long-term debts.